2017
DOI: 10.1080/10810730.2016.1258743
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk Information Sharing: The Experience of Individuals Receiving Genetic Counseling forBRCA1/2Mutations

Abstract: Genetic counseling and testing for familial cancer is a unique context for the communication of risk information in the family. This study utilized a theoretical framework based on the family systems perspective to understand intra-familial cancer risk communication patterns in the Ashkenazi Jewish population. Individuals (n=120) at an elevated risk for BRCA1/2 mutations were included. Change in communication patterns over time was assessed using McNemar tests. Associations with communication patterns were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 30 publications
1
28
1
Order By: Relevance
“…Founder mutations have previously been described for some population as in Ashkenazi Jewish population, 3% of individuals carried BRCA1 c.185delAG, BRCA1 c.5382insC or BRCA2 c.6174delT mutations (Wiesman et al, ). The frequency of BRCA1 and BRCA2 mutations varies among population (Chopra & Kelly, ). The knowledge of the spectrum of mutations and their geographical distribution could provide more efficient approach for screening protocol and allow more rapid, less expensive and more affordable genetic testing strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Founder mutations have previously been described for some population as in Ashkenazi Jewish population, 3% of individuals carried BRCA1 c.185delAG, BRCA1 c.5382insC or BRCA2 c.6174delT mutations (Wiesman et al, ). The frequency of BRCA1 and BRCA2 mutations varies among population (Chopra & Kelly, ). The knowledge of the spectrum of mutations and their geographical distribution could provide more efficient approach for screening protocol and allow more rapid, less expensive and more affordable genetic testing strategy.…”
Section: Discussionmentioning
confidence: 99%
“…These genes include ATM, TP53, CHECK2, PTEN, STK11, PALB2, BRIP, and the RAD51 genes (Merdad et al, ). In fact, the frequency of TP53 mutations among Saudi patients is one of the highest in the world (Al‐Qasem et al, ; Chopra & Kelly, ). Further researches are needed to elucidate the spectrum of mutations in those genes to confirm their association with the increase risk of developing breast cancer in the population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sharing of test results with distant relatives occurs less frequently, and those relatives do not have the opportunity for testing and cancer prevention 49 . Other factors that influence family sharing include recognition of at‐risk relatives, relationship type, physical or emotional closeness, perceptions of whether relatives want to know, anticipation of relatives’ reactions, and personal emotions 49‐51 . Health benefits from genetic testing can be magnified through development and implementation of strategies that encourage communication of genetic results, especially positive results, with at‐risk relatives 50 .…”
Section: Improving Identification Of Hereditary Cancer Predispositionmentioning
confidence: 99%
“…Other factors that influence family sharing include recognition of at‐risk relatives, relationship type, physical or emotional closeness, perceptions of whether relatives want to know, anticipation of relatives’ reactions, and personal emotions 49‐51 . Health benefits from genetic testing can be magnified through development and implementation of strategies that encourage communication of genetic results, especially positive results, with at‐risk relatives 50 . It will be important to develop and test interventions to improve the identification of HBC within families given the important public health implications and opportunity to reduce overall cancer morbidity and mortality.…”
Section: Improving Identification Of Hereditary Cancer Predispositionmentioning
confidence: 99%
“…In clinical practice, it has been observed that individuals who undergo genetic testing often perceive their freedom to choose between different options to be constrained, e.g., by family or personal circumstances (Hallowell 1999). Thus, being informed about one's individual genetic condition can raise conflicting views regarding the right not to know, individuals often are put in the position of balancing autonomy and responsibility (Chopra and Kelly 2017;Lemke 2004;Hallowell et al 2003). Both the right not to know and the right to know imply an uptake of responsibility for the resulting consequences.…”
Section: Introductionmentioning
confidence: 99%